Preparation of fructus forsythiae active site and application of fructus forsythiae active site to Parkinson disease - SONG XIUYUN; JIANG JIANSHUANG; ZHANG PEICHENG; ZHANG SHUAI; FENG ZIMING; CHEN NAIHONG; YANG YA'NAN; ZHANG FAN (2015)
The invention relates to a preparation method of a common traditional Chinese medicine of a fructus forsythiae active site. The method comprises: pulverizing a medicinal material of fructus forsythia; performing reflux extraction with a solvent, such as water or ethanol; concentrating the extracting liquid at a reduced pressure to obtain extractum; performing extraction through a plurality of organic solvents and recycling the organic solvents of the site extracted by n-butyl alcohol; dispersing and dissolving the site extracted by n-butyl alcohol in a proper amount of distilled water; taking the obtained supernate out and putting the supernate in a macroporous adsorption resin with weak polarity or medium polarity; and performing elution in a water-alcohol system to obtain the fructus forsythiae active site. According to the method, a separation method and a modern spectroscopic analysis method for a plurality of chemical components are utilized to separate and identify chemical components in the active site, thereby obtaining 15 compounds, 9 of which are new compounds. In vitro, the fructus forsythiae active site has an obvious function of preventing neurocyte damage due to rotenone, and in vivo, the fructus forsythiae active site can significantly increase the number of TH positive neuron, due to rotenone, of a substantia nigra zona compact of a rat and improve a Parkinson symptom of the rat. Therefore, the fructus forsythiae active site can be prepared into a medicine for preventing and curing the Parkinson disease.